An Ester of β‐Hydroxybutyrate Regulates Cholesterol Biosynthesis in Rats and a Cholesterol Biomarker in Humans. Issue 12 (26th October 2015) - Kemper, Martin F.; Srivastava, Shireesh; Todd King, M.; Clarke, Kieran; Veech, Richard L.; Pawlosky, Robert J.
Abstract: In response to carbohydrate deprivation or prolonged fasting the ketone bodies, β‐hydroxybutyrate (βHB) and acetoacetate (AcAc), are produced from the incomplete β‐oxidation of fatty acids in the liver. Neither βHB nor AcAc are well utilized for synthesis of sterols or fatty acids in human or rat liver. To study the effects of ketones on cholesterol homeostasis a novel βHB ester (KE) (( R )‐3‐hydroxybutyl ( R )‐3‐hydroxybutyrate) was synthesized and given orally to rats and humans as a partial dietary carbohydrate replacement. Rats maintained on a diet containing 30‐energy % as KE with a concomitant reduction in carbohydrate had lower plasma cholesterol and mevalonate (−40 and −27 %, respectively) and in the liver had lower levels of the mevalonate precursors acetoacetyl‐CoA and HMG‐CoA (−33 and −54 %) compared to controls. Whole liver and membrane LDL‐R as well as SREBP‐2 protein levels were higher (+24, +67, and +91 %, respectively). When formulated into a beverage for human consumption subjects consuming a KE drink (30‐energy %) had elevated plasma βHB which correlated with decreased mevalonate, a liver cholesterol synthesis biomarker. Partial replacement of dietary carbohydrate with KE induced ketosis and altered cholesterol homeostasis in rats. In healthy individuals an elevated plasma βHB correlated with lower plasma mevalonate.